L-System model for the growth of arbuscular mycorrhizal fungi, both within and outside of their host roots - Schnepf, A; Leitner, D; Schweiger, P F; Scholl, P; Jansa, J (Journal of the Royal Society, Interface, 2016)
Development of arbuscular mycorrhizal fungal colonization of roots and the surrounding soil is the central process of mycorrhizal symbiosis, important for ecosystem functioning and commercial inoculum applications. To improve mechanistic understanding of this highly spatially and temporarily dynamic process, we developed a three-dimensional model taking into account growth of the roots and hyphae. It is for the first time that infection within the root system is simulated dynamically and in a spatially resolved way. Comparison between data measured in a calibration experiment and simulated results showed a good fit. Our simulations showed that the position of the fungal inoculum affects the sensitivity of hyphal growth parameters. Variation in speed of secondary infection and hyphal lifetime had a different effect on root infection and hyphal length, respectively, depending on whether the inoculum was concentrated or dispersed. For other parameters (branching rate, distance between entry points), the relative effect was the same independent of inoculum placement. The model also indicated that maximum root colonization levels well below 100%, often observed experimentally, may be a result of differential spread of roots and hyphae, besides intrinsic plant control, particularly upon localized placement of inoculum and slow secondary infection.
Keywords: Mycorrhizae; Models, Biological; biologické modely; Hyphae; mykorhiza; hyfy